2020
DOI: 10.1002/cbdv.202000407
|View full text |Cite
|
Sign up to set email alerts
|

Bioherbicide Potential of Eucalyptus saligna Leaf Litter Essential Oil

Abstract: We aimed to evaluate the bioherbicide potential of Eucalyptus saligna leaf litter essential oil, its fractions and major compounds. Six essential oil fractions were obtained by preparative thin‐layer chromatography and analyzed by gas chromatography/mass spectrometry. Effects of the oil, its fractions and major compounds (1,8‐cineole and/or α‐pinene) diluted in aqueous solution were assessed on germination and seedling growth. Recipient species were Lactuca sativa (model), Amaranthus viridis (weed), Eragrostis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…1,8-Cineole is abundantly present in eucalyptus plants and is an effective treatment for pediculosis [ 15 ], as well as an efficient biological herbicide [ 16 ], antimicrobial, and antioxidant [ 17 ]. Recently, several essential oil-derived components, such as 1,8-cineole, have been reported to inhibit influenza symptoms [ 18 ] and severity of coronavirus disease 2019 (COVID-19) [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,8-Cineole is abundantly present in eucalyptus plants and is an effective treatment for pediculosis [ 15 ], as well as an efficient biological herbicide [ 16 ], antimicrobial, and antioxidant [ 17 ]. Recently, several essential oil-derived components, such as 1,8-cineole, have been reported to inhibit influenza symptoms [ 18 ] and severity of coronavirus disease 2019 (COVID-19) [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to analyse the residues of these substances and to estimate their effects on the animal organism. Carvacrol is an essential oil which has very strong antifungal, antiviral and antimicrobial effects and can reduce the population of parasites responsible for gastrointestinal diseases ( 1 , 5 , 6 , 11 , 17 , 19 , 22 , 30 ). Our previous studies also showed that carvacrol significantly impaired the growth and development of Alphitobius diaperinus larvae and is toxic to this pest ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multicomponent herbal supplements are alternatives to antibiotics in practical poultry nutrition. Many studies have demonstrated the antibacterial activity of oregano ( Origanum vulgare ), black pepper ( Piper nigrum ), clove ( Syzygium aromaticum ), thyme ( Thymus vulgaris ) and essential oil components (thymol, carvacrol, piperine, eugenol, and curcumin) against many strains of pathogenic bacteria, including Clostridium perfringens , Escherichia coli , Staphylococcus aureus , Salmonella typhimurium , Listeria monocytogenes , and Yersinia enterocolitica ( 6 , 17 , 22 , 30 ). These observations were made in in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, Eucalyptus extracts have been reported to have herbicidal effects on the seedling growth and germination of many weeds [18][19][20]. Several studies have shown the herbicidal properties of EOs against a wide variety of weeds [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%